Ultra-high photoactive thiadiazolo[3, 4-g]quinoxaline nanoparticles with active-targeting capability for deep photodynamic therapy. Issue 39 (15th September 2021) - Zhang, Li-Peng; Li, Xianqiang; Zhao, Hongyou; Kang, Lin; Liu, Shiyang; Liu, Tianlong; Zhao, Yuxia
Abstract : A novel biocompatible photosensitizer (TQs-PEG4) with an ultra-high singlet oxygen quantum yield was designed and synthesized for a deep photodynamic therapy under 660 nm laser irradiation. Abstract : Improving the effective treatment depth of photodynamic therapy (PDT) is an important issue to resolve for its clinical application. In this study, a new biocompatible photosensitizer (PS), namely TQs-PEG4, based on thiadiazolo[3, 4- g ]quinoxaline (TQ) with ultra-high photoactive property is designed and synthesized. TQs-PEG4 possesses an ultra-high singlet oxygen quantum yield ( Φ Δ = 1.04). After encapsulating it with a biodegradable copolymer (DSPE–mPEG2000–cRGD), well distributed organic TQs-PEG4 nanoparticles (NPs) are formed with good water dispersity and excellent active tumor-targeting property. In vitro PDT experiments reveal that TQs-PEG4 NPs present excellent phototoxicities towards different cancer cell lines with an ultra-low dosage (<0.3 μg mL −1 ). TQs-PEG4 NP mediated PDT significantly inhibited tumor growth even when the tumor was covered with a 6 mm thick piece of pork tissue under 660 nm laser irradiation. Both the histological analysis and biochemical testing demonstrated the good biosafety of TQs-PEG4 NPs towards mice. This study not only develops an ultra-high photoactive organic PS, TQs-PEG4, but also proves the great potential of TQs-PEG4 NPs for application in deep PDT.